The Integration of The Contextual Approach and Realia to Enhance Arabic Speaking Skills of Madrasah Aliyah Students - Fitriyatur Rosyidah; Moch. Wahib Dariyadi; Moh. Khasairi; Abd Rauf Tan Sri Hassan (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
Speaking proficiency in Arabic is a fundamental skill for Madrasah Aliyah students, yet many face challenges in developing it effectively. These difficulties are often due to the lack of contextual learning approaches and limited use of relevant teaching media. This study aimed to examine the effectiveness of a contextual learning approach supported by realia in enhancing the Arabic speaking skills of Grade X students at MAN 3 Jombang. This research employed a Classroom Action Research (CAR) design conducted in two cycles, which included stages of planning, implementation, observation, and reflection. A total of 37 students participated in this study. Data were collected through observation, interviews, speaking tests, and documentation, then analyzed using both qualitative and quantitative descriptive methods. The findings indicate that the integration of contextual learning and realia media significantly improved students' speaking performance. In the first cycle, students showed improvement in vocabulary and sentence structure. In the second cycle, notable progress was observed in fluency, self-confidence, and the ability to convey ideas orally. The use of realia—such as concrete objects and visual aids—created a more interactive and engaging learning environment that encouraged active participation in Arabic communication. This study suggests that the contextual approach combined with realia is an effective strategy to be applied more broadly in Arabic language instruction at the secondary school level.